Islamic Education with an Entrepreneurial Perspective: Building Character and Independence Among Students - Ahmad Dini; Moh. Subhan; Saehudin Saehudin (Indonesian Journal of Islamic Education and Learning, 2026)
Islamic education with an entrepreneurial perspective is a pedagogical approach that integrates Islamic values with entrepreneurial competencies to build character and independence among students. This research aims to evaluate the implementation model of Islamic education that synergizes religious and entrepreneurial learning in order to strengthen students' sense of responsibility, work ethic, creativity, and economic skills. The research method uses a multiple case qualitative approach in three leading Islamic schools in Indonesia over 12 months, with data collection techniques including in-depth interviews, participant observation, curriculum documentation, and focus group discussions. Data analysis employs the Miles & Huberman model with procedures for data reduction, data presentation, and conclusion drawing. The research findings reveal that the integration of entrepreneurship material in Islamic Education subjects can enhance students' self-efficacy, work ethic, and economic independence. The findings also affirm that Islamic education with an entrepreneurial perspective is effective in shaping ethical character and professional competence when accompanied by direct practice, school-industry collaboration, and value-based contextual modules. The implications of the research indicate that the Islamic education curriculum must be reconstructed to provide more space for entrepreneurship learning rooted in the values of monotheism, trustworthiness, and the welfare of the community as a moral foundation and contemporary economic competence.